ALAT UKUR TINGGI DAN MASSA BADAN OTOMATIS BERBASIS MIKROKONTROLLER ATMEGA 8535 - Shokhibul Kahfi; Achmad Solichan; Aris Kiswanto (PSTE UNIMUS, 2015)
ABSTRACT This combination; Automatic mass and high measurement device based on microcontroller ATMega 8535, is a combination which can measure for high and mass digitally. This combination consist of some blocks, power supply 5V and there are 2 censors; ultrasonic and optocoupler which is an input of this device, and microcontroller ATMega 8535 is as a program controller and LCD is as presenter. Censor ultrasonic HSCR-04 will detect things surrounding censor, censor radiator will send ultrasonic phase. If ultrasonic phase bounches back to the receiver, it means there is an object surroundings censor and optocoupler censor will count the hole in analog weights. Then, the second result is sent to microcontroller to be calculated to LCD to be shown. Keywords : Keywords: ultrasonic censor, optocoupler, Microcontroller ATMega 8535, LCD